An adaptive governance for water justice in Europe - Gomes, Carla (2024)
The intense droughts of the last five years, which most recently led the Portuguese Government to approve water rationing in the region of Algarve, are stark reminders of the scarcity threat looming over Europe. The increase in consumption in recent decades - from households to agriculture to industry – compounded by climate change - has contributed to a growing pressure. Water stress is not just a concern of Southern Europe anymore and has already prompted the European Commission to announce a new strategy for water resilience to be launched in 2024. The active involvement of social scientists has never been so crucial for water management as today. 20% of the European territory and 30% of Europeans are affected by water stress during an average year, according to the European Environment Agency. Droughts alone already represent an estimated loss of 9 billion euros annually, coupled with the impacts of storms and floods. It is estimated that 17 per cent of the continent’s population and 13 per cent of its GDP will be affected by a high to extreme risk of scarcity by 2050. The Organisation for Economic Co-operation and Development (OECD) has created in 2015 a set of principles for water governance, some of them especially crucial in face of the climate emergency. Policy coherence between sectors has been one of the most challenging and is paramount for implementing a circular economy across the nexus with energy, waste management and food production. The appropriate scales for governing water resources within basin systems are another key element in this governance model. Water governance has been mostly local and incremental, as noted by the Global Commission on the Economics of Water (2023), in the wake of the UN Water Conference of March 2023. To develop a new water culture, it will be crucial to cultivate trust and engagement, one of the key dimensions of the OECD model. This requires finding balanced and negotiated solutions to address the trade-offs between competing water demands (e.g., tourism vs agriculture), which come to the fore especially during intense drought episodes. The new 332 models of governance require an effective and inclusive engagement of key stakeholders, but also social actors that are most vulnerable and historically underrepresented. This communication addresses the main challenges currently facing water governance in Europe. It is based on a policy review and also draws insights from recent analyses carried out in the six countries involved in the B-WaterSmart project (H2020, Grant No. 869171) (Portugal, Italy, Spain, Belgium, Germany and Norway), regarding models of governance and social acceptability of water-smart solutions (e.g., water reuse, stormwater management). We examine the key trends towards a more adaptive, fair and participatory governance of water resources in Europe, seeking to strike a balance between local priorities and the global nature of water adaptation.